The reaction rate of radiative n8Li capture in the range from 0.01 to 10 T9 - Dubovichenko, S. B.; Yeleusheva, B. M.; Burkova, N. A.; Tkachenko, A. S. (Frontiers in Astronomy and Space Sciences, 2023)
Within the modified potential cluster model with forbidden states, the total cross sections are calculated for capture to the ground and first excited states of the 9Li nucleus in the n8Li channel in the energy range from 10-5 eV to 5 MeV based on Е1 and M1 transitions. The experimentally proved resonance at Ec.m. = 0.232 MeV in the 4P5/2 wave and ab initio predicted 4P3/2 resonance at 1.32 MeV [Phys. Rev. C 103, 035801 (2021)] are considered. The strong impact of the asymptotic constant and channel spectroscopic factors on the total capture cross sections are responsible for the variation of the absolute values within factor two. As a consequence, the thermal cross sections are 24 mb - 46.8 mb. The evaluation of based on the extrapolation of ab initio cross sections gives ~ 85 mb. The reaction rate is calculated in the temperature range from 0.01 to 10 T9. The reported reaction rates are compared at benchmark point 1T9. The comparison with two datasets [Phys. Rev. C 103, 035801 (2021) and Phys. Rev. C 105, 064608(2022)] on reaction rates recently calculated in microscopic models in extended temperature intervals shows the essential quantitative and qualitative difference. The comparative joint analysis of reaction rates of radiative neutron capture on the lithium isotopes 6,7,8Li is suggested for the choice of optimal interval for the asymptotic constants.